Filling material capable of rapidly stimulating collagen and instantly filling as well as preparation method and application of filling material
The special structure filled microspheres prepared by the Pickering emulsion method solve the problem of poor effectiveness of existing materials in stimulating collagen regeneration and instant filling, achieving faster regeneration and longer lasting period.
Patent Information
- Application Number
- CN202411611117.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-11
AI Technical Summary
The existing filling materials are not effective in stimulating collagen regeneration and instant filling. The regenerated materials are dispersed into the gel matrix after being modified. They need to be gradually absorbed and metabolized before they can stimulate regeneration, resulting in the effect of Slower effect.
The Pickering emulsion method is used to prepare filled microspheres with special structures. The surface of the microspheres is composed of solid particles. The solid particles are nano-scale regenerated material microspheres. The core is made of cross-linked supportive filler materials and is passed through microfluidic control method. and crosslink curing process preparation.
It achieves better instant filling effect and quickly stimulates collagen regeneration, enhances the support strength and degradation time of the microspheres, and improves the effectiveness of the filling material.
Smart Images

Figure CN119405885A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of soft tissue repair, and in particular relates to a filling material capable of rapidly stimulating collagen and instant filling, and a preparation method and application thereof. Background Art
[0002] Skin aging is a complex evolutionary process, which is divided into endogenous aging and exogenous aging, and is mainly manifested by skin sagging, decreased elasticity, dryness, increased wrinkles, decreased immune regulation, etc. Endogenous factors mainly include time, genetic factors and hormones, while exogenous aging factors include ultraviolet radiation, environmental pollution, living habits, etc. Healthy skin has dense collagen support and elastin traction, so the skin is plump and elastic. However, the collagen of aging skin is thin and loose, and the ability to repair elastin is also weakened, resulting in decreased elasticity and increased wrinkles.
[0003] In recent years, injectable fillers for cosmetic and medical purposes have developed rapidly. Injectable fillers can achieve the cosmetic effect of minimally invasive treatment at the injection site and have attracted attention. At present, the filling products on the market are divided into two categories: immediate filling and regeneration products. Instant filling products are mainly cross-linked hyaluronic acid microspheres, and regeneration products include PLLA microspheres, PCL microspheres, etc. In reality, the combination of the two types of products is reported in the following literature, but there are not many products actually on the market, such as: Patent CN201510593332.X discloses a hyaluronic acid mixed gel containing amphiphilic microspheres for injection and a preparation method thereof, which solves the dispersion problem of PLLA microspheres in HA gel; Patent CN202010398742.X discloses a biodegradable injectable filler, a preparation method and its application, which modifies the surface of PLLA microspheres by sodium hyaluronate to make them hydrophilic; However, the filler matrix in the above literature is an uncross-linked or slightly cross-linked HA gel, and the immediate support performance is insufficient. In addition, after the regenerative materials are modified and dispersed in the gel matrix, the regenerative materials will not be exposed until the gel matrix is gradually absorbed and metabolized, thus stimulating regeneration, making the regeneration effect slower and less effective than expected.
[0004] The inventors of the present invention hope to develop a filling material that can quickly stimulate collagen and instantly fill the skin based on the existing technology and existing products. Summary of the invention
[0005] The first technical problem solved by the present invention is to provide a filling material that can quickly stimulate collagen and fill immediately.
[0006] The filling material of the present invention is a filling microsphere with a special structure prepared by the Pickering emulsion method. The microsphere has a special Pickering structure, that is, the surface of the microsphere is composed of solid particles, the solid particles are nano-scale regenerative material microspheres, and the core of the filling microsphere is made by cross-linking the supporting filling material. The microsphere has a better instant filling effect, and the solid particles of the epidermis can contact the skin tissue at the fastest speed, so it has the effect of instant filling and rapid stimulation of collagen regeneration. In addition, the preparation of the microsphere only requires a small amount of emulsifier, which can reduce the risk of emulsifier residue.
[0007] The preparation method of the filling material of the present invention comprises the following steps:
[0008] A. Prepare nano-scale recycled material microspheres;
[0009] B. Preparation of composite microspheres by Pickering emulsion method;
[0010] C. Microsphere curing;
[0011] D. Microsphere washing.
[0012] In the above technical solution, step A satisfies at least any of the following:
[0013] The nanometer-level regenerative material microspheres described in step A are prepared by a solvent evaporation method.
[0014] The method for preparing nano-scale regenerated material microspheres described in step A is as follows: taking regenerated material, organic solvent, emulsifier, and water to prepare pre-emulsion, and adopting solvent volatilization method to prepare nano-scale regenerated material microspheres.
[0015] The preparation conditions of the solvent evaporation method described in step A are as follows: the pre-emulsion is homogenized by ultrasonic treatment to obtain a microemulsion, and the microemulsion is rapidly cooled to 20-40° C. and stored until the organic solvent is completely evaporated to obtain nano-scale regenerative material microspheres.
[0016] Preferably, the preparation conditions of the solvent volatilization method in step A are as follows: the pre-emulsion is homogenized by ultrasonic treatment to obtain a microemulsion, the microemulsion is ice-cooled to 33° C. and stored for 16 hours to completely evaporate the organic solvent to obtain nano-scale regenerative material microspheres.
[0017] Specifically, the regenerative material in step A is an amphiphilic regenerative material.
[0018] Furthermore, the amphiphilic regenerative material is selected from at least one of the hydrophilic modified materials of poly (L-lactic acid) (PLLA), poly (lactic acid-glycolic acid copolymer) (PLGA), polycaprolactone (PCL), or a mixture thereof.
[0019] The amphiphilic regeneration material used in the present invention is a block polymer, and the block molecular weight ratio of the hydrophilic and lipophilic parts is screened by the properties in water. The amphiphilic regeneration material is dispersed in water to form a 5% dispersion. After stirring at room temperature for 30-120 minutes, the dispersion still maintains good fluidity, and the viscosity has no obvious change or becomes slightly viscous, which is the best. It is preferred to use an amphiphilic regeneration material that meets the above dispersion properties.
[0020] Preferably, the amphiphilic regenerative material is selected from any one of PLLA-PEG, PCL-PEG, and PLGA-PEG; wherein PLLA, PCL, and PLGA are hydrophobic ends, and PEG is a hydrophilic end.
[0021] The molecular weight ratio of the hydrophilic part and the lipophilic part of the amphiphilic regenerative material is 1:3-1:10; more preferably, the molecular weight ratio of the hydrophilic part and the lipophilic part of the amphiphilic regenerative material is 1:3-1:8; most preferably, the molecular weight ratio of the hydrophilic part and the lipophilic part of the amphiphilic regenerative material is 1:5. If the proportion of the hydrophilic end (PEG) is too large, the stability of the emulsion prepared subsequently is poor. If the proportion of the hydrophobic end is too large, the nanoparticles are easy to fall off after the cross-linking and curing of the internal phase HA.
[0022] The molecular weight of PLLA (or PCL, PLGA) is 5000-100000, and the molecular weight of PEG is 1000-30000. More preferably, the molecular weight of PLLA (or PCL, PLGA) is 40000, and the molecular weight of PEG is 8000.
[0023] The organic solvent is selected from dichloromethane.
[0024] The emulsifier is selected from at least one of lecithin, Tween, and Span or a mixture thereof.
[0025] The amount of the emulsifier added is 1 / 3-1 of the mass of the amphiphilic regeneration material; preferably, the amount of the emulsifier added is 1 / 2 of the mass of the amphiphilic regeneration material.
[0026] The average particle size of the nano-scale recycled material microspheres prepared in step A is 80-200 nm; preferably, the average particle size of the nano-scale recycled material microspheres prepared in step A is 100 nm.
[0027] In the above technical solution, step B satisfies at least any of the following:
[0028] The composite microspheres are prepared by the Pickering emulsion method described in step B; the oil phase is used as the external phase, the aqueous solution of the supporting filler material and the cross-linking agent are used as the internal phase, and the nano-scale regenerative material microspheres and the emulsifier described in step A are used to prepare the Pickering emulsion.
[0029] The composite microspheres prepared by the Pickering emulsion method in step B are prepared by homogenous emulsification or microfluidics. The ratio of homogenous emulsification oil phase to water phase is 3:1-10:1; the homogenous emulsification shear speed is 5000-10000 r / min. Preferably, the microfluidics method is used for preparation.
[0030] The oil phase is selected from liquid paraffin + isobutyl alcohol (the weight ratio of isobutyl alcohol: liquid paraffin is 1:20-1:80, preferably 1:50, and isobutyl alcohol is an emulsifier to stabilize the emulsion) and soybean oil.
[0031] The supporting filling material is selected from one or more of sodium hyaluronate (HA), collagen, carboxymethyl chitosan, and polyamino acid.
[0032] Preferably, the supporting filling material is selected from sodium hyaluronate (HA) and collagen.
[0033] Most preferably, the supportive filler material is selected from sodium hyaluronate (HA).
[0034] The cross-linking agent is selected from one or more of glycidyl ethers, epoxides, glutaraldehyde or carbodiimide.
[0035] Preferably, the cross-linking agent glycidyl ether is selected from butanediol diglycidyl ether (BDDE).
[0036] The preparation method described in step B adopts microfluidics, and the parameter conditions are that the inner phase flow rate is 150-500 μl / h and the outer phase flow rate is 100-500 μl / min.
[0037] Preferably, the preparation method in step B adopts a microfluidic method, and the parameter conditions are that the inner phase flow rate is 300 μl / h and the outer phase flow rate is 235 μl / min.
[0038] The mass ratio of the supporting filling material in step B to the nano-scale regenerative material microspheres in step A is 1:5-1:10. The purpose of controlling the mass ratio is to avoid microsphere adhesion. When the ratio is lower than 1:5, the microspheres will adhere and aggregate. When the ratio is higher than 1:10, microfluidic channel blockage is very likely to occur.
[0039] The preferred mass ratio of the supporting filling material to the nano-scale regenerative material microspheres described in step A is 1:5.
[0040] The pH value of the internal phase obtained in step B is adjusted to 10-13; preferably, the pH value of the internal phase obtained in step B is adjusted to 12.
[0041] In the above technical solution, step C satisfies at least any of the following:
[0042] In step C, the microspheres are cured by placing the Picklerine emulsion at 25-60° C. to allow the microspheres to quickly complete cross-linking and curing.
[0043] In step C, the microspheres are cured by placing the Picklerine emulsion at 50° C. to allow the microspheres to rapidly complete cross-linking and curing.
[0044] The above temperature is to select the temperature with the fastest demulsification rate to avoid emulsion demulsification.
[0045] In the above technical solution, step D removes excess impurities by washing, and at least one of the following is satisfied:
[0046] Step D: The microspheres obtained in step C are dialyzed in PBS buffer for 24-72 hours to obtain a filling material.
[0047] Step D: The microspheres obtained in step C are dialyzed in PBS buffer for 48 hours to obtain a filling material.
[0048] The purpose of washing the microspheres in step D is to remove excess impurities and prevent surface particles from falling off, thereby obtaining filled microspheres with a special structure.
[0049] The filling material of the present invention uses isobutyl alcohol and liquid paraffin as the oil phase, nano-scale regenerative material microspheres and an emulsifier as the external phase, and a supporting filling material aqueous solution and a cross-linking agent as the internal phase, and is prepared by cross-linking, curing, and washing after the Pickering emulsion is prepared. The ratio of each component is as follows:
[0050] The external phase is composed of the following components in the following mass ratios: nanometer regeneration material microspheres: 1-10 parts; emulsifier: 1-5 parts; isobutyl alcohol: 1-10 parts; liquid paraffin: 10-200 parts.
[0051] The inner phase is composed of the following components in the following mass ratios: supporting filling material: 1-20 parts; cross-linking agent: 1-5 parts; water: 1-500 parts, and the pH value of the inner phase is adjusted to 10-13.
[0052] Mass ratio of inner phase to outer phase: 1:10-1:100.
[0053] Preferably, the ratio of each component is as follows:
[0054] The external phase is composed of the following components in the following mass ratios: nano-regenerative material microspheres: 1 part; emulsifier: 1 part; isobutyl alcohol: 2 parts; liquid paraffin: 100 parts.
[0055] The inner phase is composed of the following components in the following mass ratios: supporting filling material: 10 parts; cross-linking agent: 1 part; water: 240 parts, and the pH value of the inner phase is adjusted to 12.
[0056] Mass ratio of inner phase to outer phase: 1:40-1:50.
[0057] With HA as the supporting filling material, the inner phase solution is composed of the following components in the following weight ratio:
[0058] 1-10 parts of supporting filling material
[0059] Crosslinking agent 0.1-1 part
[0060] 50-100 parts of water.
[0061] Preferably, HA is used as the supporting filler material, and the inner phase solution is composed of the following components in the following weight ratio:
[0062] 4 parts of supporting filling material aqueous solution
[0063] Crosslinking agent 0.4 parts
[0064] 94.6 parts of water.
[0065] Collagen is used as the supporting filling material, and the inner phase solution is composed of the following components in the following weight ratios:
[0066] 5-20 copies of supporting filling material
[0067] Crosslinking agent 0.5-5 parts
[0068] 50-100 parts of water.
[0069] Preferably, collagen is used as the supporting filling material, and the inner phase solution is composed of the following components in the following weight ratio:
[0070] 8 parts of supporting filling material aqueous solution
[0071] 1 part crosslinking agent
[0072] 90 parts of water.
[0073] Using PLLA-PEG block polymer as raw material, the nano-scale regenerative material microspheres are made of the following components in weight ratio:
[0074] PLLA-PEG 1-10 parts
[0075] Solvent (dichloromethane) 50-100 parts
[0076] Emulsifier (lecithin) 0.1-5 parts.
[0077] Preferably, the nanometer-level regenerative material microspheres prepared by using PLLA-PEG block polymer as raw material are composed of the following components in weight ratio:
[0078] PLLA-PEG 3 parts
[0079] Solvent (dichloromethane) 95 parts
[0080] Emulsifier (lecithin) 2 parts.
[0081] The nano-scale regenerative material microspheres are prepared using PCL-PEG block polymer as raw material, and are composed of the following components in weight ratio:
[0082]
[0083] Preferably, the PCL-PEG block polymer is used as a raw material to prepare nano-scale regenerative material microspheres, which are composed of the following components in weight ratio:
[0084]
[0085] Another technical problem solved by the present invention is to provide a use of the filling material of the present invention in preparing a soft tissue repair product.
[0086] The beneficial effects of the filling material of the present invention are as follows: (1) Improving the strength of immediate filling and providing better supporting performance; (2) Accelerating the direct contact time between the regenerative material and the tissue, thereby stimulating tissue regeneration more quickly; (3) Prolonging the degradation time and improving the duration of effect.
[0087] The filling material of the present invention is covered with nanoparticles on the surface of the microspheres. Due to the amphiphilicity of the nanoparticles, the hydrophilic group -OH can participate in the cross-linking and curing process after the emulsion is formed, making it difficult to fall off. The filling material of the present invention has a better instant filling effect. The solid particles of the epidermis can contact the skin tissue at the fastest speed, increasing the supporting performance of the medical and aesthetic filling material, so it has the effect of instant filling and rapid stimulation of collagen regeneration. In addition, the preparation of the filling material does not require the addition of an additional emulsifier, reducing the risk of residues. BRIEF DESCRIPTION OF THE DRAWINGS
[0088] Figure 1 This is a diagram illustrating the preparation method of the filling material of the present invention.
[0089] Figure 2 This is a diagram of the emulsion morphology of the filling material of the present invention.
[0090] Figure 3 It is the degradation rate diagram of Example 1 and Comparative Example 1.
[0091] Figure 4 This is the emulsion morphology diagram of the filling material of Comparative Example 2.
[0092] Figure 5 This is a picture of Sirius red staining of type I collagen fiber and type III collagen fiber;
[0093] Among them, AE are Example 1, Example 2, Example 3, homemade PLLA microspheres, and commercially available samples, respectively. DETAILED DESCRIPTION
[0094] The scheme of the present invention will be explained and described below in conjunction with the examples but the present invention is not limited thereto. It will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the examples, the techniques or conditions described in the literature in this area or the product specifications are followed. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be obtained commercially.
[0095] The present invention provides a filling material obtained by preparing a pickling emulsion, cross-linking, curing and washing the pickling emulsion, using an oil phase as an external phase, a supporting filling material aqueous solution and a cross-linking agent as an internal phase, and nano-level regenerative material microspheres as an emulsifier.
[0096] The following are the definitions of the English abbreviations and main terms used in this invention:
[0097] 1. Poly-L-lactic acid, also known as poly-L-lactic acid, abbreviated as PLLA in English, has good biocompatibility and is mainly used in surgical sutures, dentistry, ophthalmology, pharmaceutical controlled release systems, artificial skin, artificial blood vessels, bone and soft tissue defect fillers, bioabsorbable scaffolds and other medical fields.
[0098] 2. Polycaprolactone (PCL) is a biocompatible, biodegradable and bioabsorbable polymer widely used in surgical sutures, artificial blood vessels / skin, bone and soft tissue fillers and tissue scaffolds. Similar to PLLA, the final degradation product of PCL is CO 2 and H 2 O, they can be completely eliminated from the body.
[0099] 3. Poly(lactic-co-glycolic acid) (PLGA) is a biodegradable functional polymer organic compound formed by random polymerization of two monomers, lactic acid and glycolic acid. It has good biocompatibility, non-toxicity, good capsule and film-forming properties, and is widely used in pharmaceutical, medical engineering materials and modern industrial fields. The preparation of PLGA mostly adopts the ring-opening polymerization method. The common ring-opening polymerization is to dehydrate and cyclize glycolic acid and lactic acid respectively to synthesize two monomers, glycolide (GA) and lactide (LA), and then obtain PLGA random copolymer by ring-opening polymerization of GA and LA.
[0100] 4. Sodium hyaluronate (HA), hyaluronic acid, also known as hyaluronic acid, can keep the skin moisturized, smooth, delicate, tender and elastic. It has the functions of anti-wrinkle, anti-wrinkle, beauty care and restoring skin physiological functions.
[0101] 5. 1,4-Butanediol diglycidyl ether (BDDE), its Chinese alias is 1,4-butanediol diglycidyl ether.
[0102] 6. Polyethylene glycol (PEG) is a high molecular polymer with the chemical formula HO(CH 2 CH 2 O)nH, non-irritating, slightly bitter, has good water solubility, and has good compatibility with many organic components. It has excellent lubricity, moisture retention, dispersibility, and adhesion.
[0103] 7. PBS solution is also called phosphate buffer solution, generally Na 2 HPO 4 and KH 2 PO 4 Preparation, because sodium salt dissolves slowly. According to the different pH solutions, weigh different masses of phosphates, or use a pH meter to adjust the pH of the solution. PBS is generally used as a supporting electrolyte. The pH value of PBS solution is about 7.4. Take 38.0g of sodium dihydrogen phosphate and 5.04g of disodium hydrogen phosphate, add water to make 1000ml, and you have it.
[0104] The inventors obtained through screening experiments that the preparation method of the filling material of the present invention comprises the following steps:
[0105] A. Prepare nano-scale recycled material microspheres;
[0106] B. Preparation of composite microspheres by Pickering emulsion method;
[0107] C. Microsphere curing;
[0108] D. Microsphere washing.
[0109] Specifically, an oil phase, nano-scale regenerative material microspheres, and an emulsifier are used as the external phase, and a supporting filler material aqueous solution and a crosslinking agent are used as the internal phase to prepare a Pickering emulsion, which is then crosslinked, solidified, and washed. Figure 1 As shown, the filling material of the present invention uses PLLA-PEG to prepare nano-scale regenerative material microspheres, HA as a supporting filling material, BDDE as a cross-linking agent, and a microfluidic method to prepare a pickler emulsion. After solidification and washing, a filling material with nanoparticles on the surface of the microspheres can be obtained. This special structure is the key to the filling material of the present invention having the effects of instant filling and rapid stimulation of collagen regeneration.
[0110] The following is a screening experiment of the main raw materials, dosage and process parameters of the filled microspheres of the present invention.
[0111] Screening experiment 1:
[0112] PLLA-PEG block polymer ratio selection: PLLA:PEG ratio 8:1-3:1, actual use ratio 5:1.
[0113] Selection basis: The amphiphilic regenerative material is a block polymer, and the block ratio of the hydrophilic and lipophilic parts is screened by the properties in water. Take the amphiphilic material and disperse it in water to form a 5% dispersion. After stirring at room temperature for 30-120 minutes, the dispersion still maintains good fluidity, and the viscosity has no obvious change or becomes slightly viscous, which is the best.
[0114] Screening experiment 2:
[0115] The mass ratio of HA to PLLA-PEG nanospheres: the actual usage ratio is 1:5.
[0116] In this parameter, three ratios of 1:1, 1:3, and 1:5 were tried. In the emulsion preparation process, the emulsions of 1:1 and 1:3 were demulsified due to insufficient emulsifier dosage of nanoparticles, resulting in droplet aggregation and uneven size. When the ratio was 1:5, there was no obvious aggregation of the emulsion, and the size of the solidified microspheres formed was uniform, such as Figure 2 As can be seen from the figure, the size of the prepared microspheres is uniformly distributed between 300-350 μm, and there is no adhesion between the microspheres, and the dispersion is good.
[0117] Example 1 Preparation process Figure 1 .
[0118] 1. Preparation of nano-scale regenerative material microspheres: Take 3 parts of PLLA-PEG and dissolve them in 95 parts of dichloromethane to form a solution, add 2 parts of emulsifier lecithin and mix well, add distilled water to the solution, and stir the mixture to form a pre-emulsion. The prepared pre-emulsion is homogenized by ultrasonic treatment and cooled with ice. The obtained microemulsion is stored at 33°C for 16 hours to completely evaporate the organic solvent to obtain nano PLLA-PEG microspheres.
[0119] 2. Preparation of composite microspheres by Pickering emulsion method: 4 parts of HA and 0.4 parts of cross-linking agent BDDE were dissolved in 94.6 parts of water to form an internal phase, and the pH value of the internal phase was adjusted to 12.
[0120] Another portion of PLLA-PEG microspheres was dispersed in a mixed solution of 100 portions of liquid paraffin and 2 portions of isobutanol, and 1 portion of Span 80 was added and mixed to form the external phase.
[0121] The mass ratio of the inner phase to the outer phase was 1:45, and the preparation method was microfluidics to prepare the picklerine emulsion, with an inner phase flow rate of 300 μl / h and an outer phase flow rate of 235 μl / min.
[0122] 3. Microsphere curing: Place the emulsion at 50°C to allow the microspheres to quickly complete cross-linking and curing.
[0123] 4. Microsphere washing: The solidified microspheres were washed in PBS buffer through a dialysis bag for 48 hours, and the washing medium was replaced regularly during this period.
[0124] Comparative Example 1: Preparation of microspheres without nanoparticles, 4 parts of HA and 0.4 parts of crosslinker BDDE were dissolved in 94.6 parts of water to form an internal phase, and the internal phase was adjusted to pH 12. Another 1 part of PLLA-PEG microspheres was dispersed in a mixed solution of 100 parts of liquid paraffin and 2 parts of isobutanol, and 1 part of Span 80 was added and mixed as the external phase. The mass ratio of the internal phase to the external phase was 1:45. The preparation method was microfluidics, and the pickling emulsion was prepared. The internal phase flow rate was 300μl / h and the external phase flow rate was 235μl / min. . The emulsion was placed at 50°C to allow the microspheres to quickly complete crosslinking and curing. The cured microspheres were washed in PBS buffer for 48h through a dialysis bag, and the washing and washing media were replaced on time during the period.
[0125] The shear storage modulus (G') data of the microspheres tested in Example 1 and Comparative Example 1 under the same conditions are shown in the following table.
[0126] Table 1 shows the G' data of Test Example 1 and Comparative Example 1.
[0127] Group G'(Pa) G”(Pa) Frequency (Hz) HA microspheres alone (Comparative Example 1) 489.261 132.312 0.1 Pickering composite PLLA-PEG-HA microspheres (Example 1) 596.385 181.003 0.1
[0128] The supporting performance of the filling material can be measured by the G' data. G' stands for the shear storage modulus, which is an important parameter for measuring the elasticity and viscosity of the material. It reflects the material's ability to resist deformation when subjected to force. The larger the G' value, the better the supporting performance of the material, which is suitable for deep filling and areas that require strong support. Choosing materials with larger G' values can ensure a more natural and lasting filling effect. In the experiment, the G' (Pa) of the single HA microsphere was 489.261Pa, while the G' (Pa) of the composite microsphere was 596.385Pa, indicating better supporting performance.
[0129] The in vitro degradation of Example 1 and Comparative Example 1 was tested according to the following method:
[0130] About 10 mg of the filled microspheres of Example 1 and the HA gel microspheres of Comparative Example 1 were accurately weighed in a vial, 1 ml of 0.5 mol / L sulfuric acid solution was added, and the solution was placed in a (95±5)°C incubator to heat the solution to completely dissolve the microspheres. 1 ml of 1 mol / L sodium hydroxide solution was added, and the mixture was thoroughly shaken and mixed. 1 ml of the solution was aspirated and placed in a vial. The total HA content in 10 mg of the filled microspheres of Example 1 and the HA gel microspheres of Comparative Example 1 was tested.
[0131] Weigh HAase solution (10000U / ml) and add it to a vial, add water and mix evenly to obtain a 150U / ml HAase aqueous solution; accurately weigh about 10mg of the filling microspheres of Example 1 and the HA gel microspheres of Comparative Example 1 in the vials, add 2ml of 150U / ml HAase aqueous solution, seal and place in a 37°C constant temperature drying oven, take out a sample at regular intervals, boil in water for 30min to remove the enzyme, centrifuge at 10000 rpm for 20min, take 1ml of the supernatant in the vial to test the HA content of the supernatant.
[0132] The degradation rate is obtained by dividing the HA content in the supernatant by the total HA content in the microspheres. Figure 3 By comparison, it can be seen that the degradation rate of comparative example 1, i.e., HA gel microspheres, under the action of enzymes in vitro is relatively fast, and the degradation rate can reach more than 80% in 96 hours; while the degradation rate of Example 1 is only 68% in 4 days, indicating that the degradation rate of HA microspheres prepared by the Pickering emulsion method is slower and lasts longer.
[0133] Comparative Example 2:
[0134] 1. Preparation of nano-scale regenerative material microspheres: Take 3 parts of PLLA-PEG and dissolve them in 95 parts of dichloromethane to form a solution, add 2 parts of emulsifier lecithin and mix well, add distilled water to the solution, and stir the mixture to form a pre-emulsion. The prepared pre-emulsion is homogenized by ultrasonic treatment and cooled with ice. The obtained microemulsion is stored at 33°C for 16 hours to completely evaporate the organic solvent to obtain nano PLLA-PEG microspheres.
[0135] 2. Preparation of composite microspheres by Pickering emulsion method: 4 parts of HA and 0.4 parts of cross-linking agent BDDE were dissolved in 94.6 parts of water to form an internal phase, and the pH value of the internal phase was adjusted to 12.
[0136] Another 0.3 parts of PLLA-PEG microspheres were dispersed in a mixed solution of 100 parts of liquid paraffin and 2 parts of isobutanol, and 1 part of Span 80 was added and mixed to form the external phase.
[0137] The mass ratio of the inner phase to the outer phase was 1:45, and the preparation method was microfluidics to prepare the picklerine emulsion, with an inner phase flow rate of 300 μl / h and an outer phase flow rate of 235 μl / min.
[0138] 3. Microsphere curing: Place the emulsion at 50°C to allow the microspheres to quickly complete cross-linking and curing.
[0139] 4. Microsphere washing: The solidified microspheres were washed in PBS buffer through a dialysis bag for 48 hours, and the washing medium was replaced regularly during this period.
[0140] Comparative Example 1 and Comparative Example 2, the obtained emulsion is as follows Figure 4 By comparison, it can be seen that the microspheres in Comparative Example 2 demulsified and aggregated, and the structure was irregular after curing, and the preparation effect was not good. Figure 4 It can be seen that the emulsion of microspheres is severely adhered and cannot be separated, and the particle sizes are different, with obvious demulsification and aggregation.
[0141] Comparative Example 3:
[0142] 1. Preparation of nano-scale regenerative material microspheres: Take 3 parts of PLLA-PEG and dissolve them in 95 parts of dichloromethane to form a solution, add 2 parts of emulsifier lecithin and mix well, add distilled water to the solution, and stir the mixture to form a pre-emulsion. The prepared pre-emulsion is homogenized by ultrasonic treatment and cooled with ice. The obtained microemulsion is stored at 33°C for 16 hours to completely evaporate the organic solvent to obtain nano PLLA-PEG microspheres.
[0143] 2. Preparation of composite microspheres by Pickering emulsion method: 4 parts of HA and 0.4 parts of cross-linking agent BDDE were dissolved in 94.6 parts of water to form an internal phase, and the pH value of the internal phase was adjusted to 12.
[0144] Another 2 parts of PLLA-PEG microspheres were dispersed in a mixed solution of 100 parts of liquid paraffin and 2 parts of isobutanol, and 1 part of Span 80 was added and mixed to form the external phase.
[0145] The mass ratio of the inner phase to the outer phase was 1:45, and the preparation method was microfluidics to prepare the picklerine emulsion, with an inner phase flow rate of 300 μl / h and an outer phase flow rate of 235 μl / min.
[0146] Under the conditions of Comparative Example 3, the microfluidic device was severely clogged and microspheres could not be successfully prepared.
[0147] Example 2
[0148] 1. Preparation of nano PCL-PEG microspheres: Take 3 parts of PCL-PEG and dissolve them in 93.5 parts of DMF: dichloromethane mass ratio = 1:2 solution to form a solution, add 0.5 parts of emulsifier Tween 20 and 3 parts of Span 80 to mix thoroughly. Add distilled water to the solution and stir the mixture to form a pre-emulsion. The prepared pre-emulsion is homogenized by ultrasonic treatment and cooled with ice. The obtained microemulsion is stored at 40°C for 12 hours to completely evaporate the organic solvent to obtain nano PCL-PEG microspheres.
[0149] 2. Preparation of composite microspheres by Pickering emulsion method: 8 parts of collagen and 1 part of cross-linking agent glutaraldehyde were dissolved in 90 parts of water to form an inner phase, and the pH value of the inner phase was adjusted to 12.
[0150] Another portion of PCL-PEG microspheres was dispersed in 100 portions of soybean oil, and 1.5 portions of Span 80 was added and mixed to form the external phase.
[0151] The mass ratio of the inner phase to the outer phase was 1:45, and the preparation method was microfluidics to prepare the picklerine emulsion. The flow rate of the inner phase was 500 μl / h, and the flow rate of the outer phase was 300 μl / min.
[0152] 3. Microsphere curing: Place the emulsion at 40°C and adjust the pH to acidic to allow the microspheres to quickly complete cross-linking and curing.
[0153] 4. Microsphere washing: The solidified microspheres were washed in PBS buffer through a dialysis bag for 48 h, during which the washing medium was replaced on schedule.
[0154] Example 3
[0155] 1. Preparation of nano PLGA-PEG microspheres: Take 3 parts of PLGA-PEG and dissolve them in 93.5 parts of DMF: dichloromethane mass ratio = 1:2 solution to form a solution, add 0.5 parts of Tween 20 and 3 parts of Span 80 as emulsifiers and mix them thoroughly. Add distilled water to the solution and stir the mixture to form a pre-emulsion. The prepared pre-emulsion is homogenized by ultrasonic treatment and cooled with ice. The obtained microemulsion is stored at 50°C for 12 hours to completely evaporate the organic solvent to obtain nano PLGA-PEG microspheres.
[0156] 2. Preparation of carboxymethyl chitosan microspheres by Pickering emulsion method: 5 parts of carboxymethyl chitosan and 0.5 parts of cross-linking agent glutaraldehyde were dissolved in 94 parts of water to form an internal phase, and the pH value of the internal phase was adjusted to 12.
[0157] Another portion of PLGA-PEG microspheres was dispersed in 100 portions of soybean oil, and 1 portion of Span 80 and 0.2 portions of Tween 20 were added and mixed to form the external phase.
[0158] The mass ratio of the inner phase to the outer phase is 1:45, and the preparation method is a homogenous stirring emulsification method to prepare the Pickering emulsion.
[0159] 3. Microsphere curing: Place the emulsion at 40-50°C to allow the microspheres to quickly complete cross-linking and curing.
[0160] 4. Microsphere washing: The solidified microspheres were washed in PBS buffer through a dialysis bag for 72 h, during which the washing medium was replaced regularly.
[0161] Animal experiments were conducted with Examples 1-3, homemade PLLA microspheres and commercially available samples. The soft tissue distribution of the filler was observed at Day 3, 1W, 2W, 3W, 4W, 6W and 8W after injection. Masson staining of the tissue at the filling site: image acquisition of the slices. All tissues were observed at low magnification for each slice, and then 2 areas were selected at 200 times to acquire images according to the size and expression of the tissues. The fibrous tissue area (Area) in the acquired images was determined using the Image-Pro Plus 6.0 image analysis system, and the percentage of fibrous tissue expression area was calculated = fibrous tissue area / field of view area (pixel area). The statistical results of the collagen fiber pixel area of the filler tissue Masson staining are shown in Table 2.
[0162] Table 2 Pixel area of collagen fibers in filler tissue stained by Masson staining
[0163] Masson Day 3 1W 2W 3W 4W 6W 8W Example 1 0.75 1.23 2.62 1.86 4.24 4.99 5.73 Example 2 0.78 1.09 0.92 2.17 3.15 3.28 4.31 Example 3 1.07 0.73 1.62 1.66 4.24 2.99 5.13 Homemade PLLA microspheres 0.05 0.29 0.72 1.17 1.15 3.28 3.35 Commercially available samples 0.33 0.69 0.55 1.66 1.99 3.59 4.68
[0164] The statistical results of collagen fiber pixel area of Masson staining of filler tissue in Table 2 show that in the late injection period (8 weeks), the expression of collagen fibers in Examples 1, 2, and 3 groups was better than that of homemade PLLA microspheres and similar to that of commercially available samples, and was better than that of homemade PLLA microspheres and commercially available samples at Day 3, 1, 2, 3, and 4 weeks, indicating that Examples 1 / 2 / 3 have a faster onset time in stimulating collagen regeneration;
[0165] Sirius red staining: The slices were imaged using a digital trinocular camera microscope plus a filter system. The expression of type I collagen and type III collagen in the images collected after 8 weeks of observation was as follows: Figure 5 .
[0166] Figure 5 From AE, they are Example 1, Example 2, Example 3, homemade PLLA microspheres, and commercially available samples. The results of the pixel area of type I collagen fibers and type III collagen fibers stained with Sirius red in the filler tissue at week 8 showed that Example 1 and Example 3 were slightly better than Example 2 and commercially available samples, and better than homemade PLLA microspheres. This shows that the examples have certain advantages in stimulating collagen regeneration.
[0167] In summary, the filling microspheres of the present invention can enhance the support strength of the microspheres: the presence of the regenerative material microspheres improves the support strength of the filling microspheres, and better achieves an instant filling effect. Moreover, the filling microspheres of the present invention have a better instant filling effect, and the solid particles of the epidermis can contact the skin tissue at the fastest speed, so they have the effects of instant filling and rapid stimulation of collagen regeneration. In addition, the degradation time is increased, and the lasting effect period is improved.
Claims
1. A method for preparing a filling material, characterized in that: The filling material uses an oil phase, nano-scale regenerative material microspheres, and an emulsifier as an external phase, and a supporting filling material aqueous solution and a cross-linking agent as an internal phase, and is prepared by cross-linking, curing, and washing after the Pickering emulsion is prepared, and includes the following steps: A. Prepare nano-scale recycled material microspheres; B. Preparation of composite microspheres by Pickering emulsion method; C. Microsphere curing; D. Microsphere washing.
2. The method for preparing the filling material according to claim 1, characterized in that: Step A satisfies at least one of the following: The preparation of nano-scale regenerative material microspheres in step A is carried out by a solvent evaporation method; The method for preparing nano-scale recycled material microspheres in step A is as follows: taking recycled material, organic solvent, emulsifier, and water to prepare a pre-emulsion, and using a solvent volatilization method to prepare nano-scale recycled material microspheres; The preparation conditions of the solvent evaporation method described in step A are as follows: the pre-emulsion is homogenized by ultrasonic treatment to obtain a microemulsion, and the microemulsion is rapidly cooled to 20-40° C. and stored until the organic solvent is completely evaporated to obtain nano-scale regenerative material microspheres; Preferably, the preparation conditions of the solvent evaporation method in step A are as follows: the pre-emulsion is homogenized by ultrasonic treatment to obtain a microemulsion, the microemulsion is cooled to 33° C. and stored for 16 hours to completely evaporate the organic solvent to obtain nano-scale regenerative material microspheres; Specifically, the regenerative material in step A is an amphiphilic regenerative material; Further, the amphiphilic regenerative material is selected from at least one of the hydrophilic modified materials of poly-L-lactic acid (PLLA), poly-lactic acid-co-glycolic acid (PLGA), polycaprolactone (PCL), or a mixture thereof; The amphiphilic regenerative material is selected from any one of PLLA-PEG, PCL-PEG, and PLGA-PEG; Furthermore, in the amphiphilic regenerative material, the PLLA end, PCL end, and PLGA end are lipophilic parts, and the PEG end is a hydrophilic part; Furthermore, the molecular weight ratio of the hydrophilic part and the lipophilic part of the amphiphilic regenerative material is 1:3-1:10; Further preferably, the molecular weight ratio of the hydrophilic part and the lipophilic part of the amphiphilic regenerative material is 1:3-1:8; Most preferably, the molecular weight ratio of the hydrophilic part to the lipophilic part of the amphiphilic regenerative material is 1:5; The molecular weights of the PLLA end, PCL end, and PLGA end are 5000-100000; Further preferably, the molecular weight of the PLLA end, the PCL end, and the PLGA end is 40,000; The molecular weight of the PEG end is 1000-30000; Further preferably, the molecular weight of the PEG end is 8000; The organic solvent is selected from dichloromethane; The emulsifier is selected from at least one of lecithin, Tween, and Span or a mixture thereof; The amount of the emulsifier added is 1 / 3-1 of the mass of the amphiphilic regeneration material; preferably, the amount of the emulsifier added is 1 / 2 of the mass of the amphiphilic regeneration material; The average particle size of the nano-scale regenerative material microspheres prepared in step A is 80-200 nm; Preferably, the average particle size of the nano-scale regenerative material microspheres prepared in step A is 100 nm.
3. The method for preparing the filling material according to claim 1, characterized in that: Step B satisfies at least one of the following: The composite microspheres are prepared by the Pickering emulsion method described in step B; the oil phase is used as the external phase, the aqueous solution of the supporting filler material and the cross-linking agent are used as the internal phase, and the nano-scale regenerative material microspheres and the emulsifier described in step A are used to prepare the Pickering emulsion; The Pickering emulsion method for preparing the composite microspheres in step B is prepared by homogenization emulsification method or microfluidics method; Wherein, the homogenization emulsification method is adopted, and the ratio of the oil phase to the water phase is 3:1-10:1; The homogenization and emulsification shear speed is 5000-10000r / min; Preferably, the microfluidic method is used for preparation; The oil phase is selected from a mixture of liquid paraffin and isobutyl alcohol, and soybean oil; Preferably, the oil phase is selected from a mixture of liquid paraffin and isobutyl alcohol, and the weight ratio thereof is 1:20-1:80; Further preferably, the oil phase is selected from a mixture of liquid paraffin and isobutyl alcohol, the weight ratio of which is 1:50; The supporting filling material is selected from one or more of sodium hyaluronate, collagen, carboxymethyl chitosan, and polyamino acid; Preferably, the supporting filling material is selected from sodium hyaluronate and collagen; Most preferably, the supportive filling material is selected from sodium hyaluronate; The cross-linking agent is selected from one or more of glycidyl ethers, epoxides, glutaraldehyde or carbodiimide; Preferably, the cross-linking agent glycidyl ether is selected from butanediol diglycidyl ether; The preparation method described in step B adopts microfluidics, and the parameter conditions are that the flow rate of the inner phase is 150-500 μl / h, and the flow rate of the outer phase is 100-500 μl / min; Preferably, the preparation method in step B adopts a microfluidic method, and the parameter conditions are that the inner phase flow rate is 300 μl / h and the outer phase flow rate is 235 μl / min; The mass ratio of the supporting filling material in step B to the nano-scale regenerative material microspheres in step A is 1:5-1:10; The preferred mass ratio of the supporting filling material to the nano-scale regenerative material microspheres described in step A is 1:5; The internal phase obtained in step B is adjusted to a pH value of 10-13; Preferably, the pH value of the internal phase obtained in step B is adjusted to 12.
4. The method for preparing the filling material according to claim 1, characterized in that: Step C satisfies at least one of the following: The microsphere curing in step C is to place the Pickering emulsion at 25-60° C. to allow the microspheres to quickly complete cross-linking and curing; Preferably, the microsphere curing in step C is to place the Picklerine emulsion at 50° C. to allow the microspheres to quickly complete cross-linking and curing.
5. The method for preparing the filling material according to claim 1, characterized in that: Step D removes excess impurities by washing, and at least one of the following is satisfied: Step D: dialyzing the microspheres obtained in step C in PBS buffer for 24-72 hours to obtain a filling material; Preferably, in step D, the microspheres obtained in step C are dialyzed in PBS buffer for 48 hours to obtain a filling material.
6. The method for preparing the filling material according to claim 1, characterized in that: The external phase is composed of the following components in mass ratio: nano-regeneration material microspheres: 1-10 parts; emulsifier: 1-5 parts; isobutyl alcohol: 1-10 parts; liquid paraffin: 10-200 parts; The inner phase is composed of the following components in the following mass ratios: supporting filler material: 1-20 parts; cross-linking agent: 1-5 parts; water: 1-500 parts, and the pH value of the inner phase is adjusted to 10-13; Among them, the mass ratio of inner phase to outer phase is 1:10-1:
100.
7. The method for preparing the filling material according to claim 6, characterized in that: The external phase is composed of the following components in the following mass ratios: 1 part of nano-regeneration material microspheres; 1 part of emulsifier; 2 parts of isobutyl alcohol; 100 parts of liquid paraffin; The inner phase is composed of the following components in the following mass ratios: supporting filler material: 10 parts; cross-linking agent: 1 part; water: 240 parts, and the pH value of the inner phase is adjusted to 12; Among them, the mass ratio of inner phase to outer phase is 1:40-1:
50.
8. The method for preparing the filling material according to claim 6, characterized in that: At least one of the following (1) to (8) is met: (1) HA is used as the supporting filling material, and the inner phase solution is composed of the following components in weight ratio: 1-10 parts of supporting filling material Crosslinking agent 0.1-1 part 50-100 parts of water; (2) Preferably, HA is used as the supporting filler material, and the inner phase solution is composed of the following components in the following weight ratio: 4 parts of supporting filling material aqueous solution Crosslinking agent 0.4 parts Water 94.6 parts; (3) Collagen is used as the supporting filling material, and the inner phase solution is composed of the following components in the following weight ratios: 5-20 copies of supporting filling material Crosslinking agent 0.5-5 parts 50-100 parts of water; (4) Preferably, collagen is used as the supporting filling material, and the inner phase solution is composed of the following components in the following weight ratios: 8 parts of supporting filling material aqueous solution 1 part crosslinking agent 90 parts of water; (5) Using PLLA-PEG block polymer as raw material, nano-scale regenerative material microspheres are prepared, which are composed of the following components in weight ratio: PLLA-PEG 1-10 parts The solvent is 50-100 parts of dichloromethane The emulsifier is 0.1-5 parts of lecithin; (6) Preferably, the nanometer-scale regenerative material microspheres prepared by using PLLA-PEG block polymer as raw material are composed of the following components in weight ratio: PLLA-PEG 3 parts The solvent is 95 parts of dichloromethane The emulsifier uses 2 parts of lecithin; (7) Using PCL-PEG block polymer as raw material, nano-scale regenerative material microspheres are prepared, which are composed of the following components in weight ratio: (8) Preferably, the PCL-PEG block polymer is used as a raw material to prepare nano-scale regenerative material microspheres, which are composed of the following components in weight ratio:
9. The filling material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the filling material according to claim 9 in preparing soft tissue repair products.
Citation Information
Patent Citations
Injection amphiphilic-microsphere-containing hyaluronic acid mixed gel and preparation method thereof
CN105126166A
Biodegradable injection fillers, their preparation methods, and their applications
CN111617315B